The Effect of Addition Vitamin E on Catfish Oil Stability - Clara Maria Kusharto; Mia Srimiati; Ikeu Tanziha; Sugeng Heri Suseno (Jurnal Pengolahan Hasil Perikanan Indonesia, 2015)
Unsaturated fatty acids contained oils which sensitive to oxidation caused by heat, light andoxygen. The oxidized oil known harmful to the body. One of the effort to prevent the oxidationprocess is by adding antioxidants stability of oil catfish and shelf life of the oil. The experimentalstudy was applied by adding vitamin E to the oil as much as 0.67 mg / g PUFA compared with thecontrol oil. Oil was stored with the Schaal Oven Test method, which are stored at a temperatureof 600C. The study showed that, based on the parameters of oxidation (free fatty acids, peroxidevalue, anisidin numbers, and the number of total oxidation), catfish oil were added vitamin Emore stabilized than the catfish oil without added vitamin E. The catfish fish oil in the form of softgell capsules added vitamin E could maintain stability in appropriate with IFOS up to 23 months.Keywords: Catfish oil, vitamin E, stability, Schaal Oven Test